2018
DOI: 10.1038/s41467-018-03088-0
|View full text |Cite
|
Sign up to set email alerts
|

A defensin-like protein drives cadmium efflux and allocation in rice

Abstract: Pollution by heavy metals limits the area of land available for cultivation of food crops. A potential solution to this problem might lie in the molecular breeding of food crops for phytoremediation that accumulate toxic metals in straw while producing safe and nutritious grains. Here, we identify a rice quantitative trait locus we name cadmium (Cd) accumulation in leaf 1 (CAL1), which encodes a defensin-like protein. CAL1 is expressed preferentially in root exodermis and xylem parenchyma cells. We provide evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
194
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 298 publications
(205 citation statements)
references
References 51 publications
9
194
1
1
Order By: Relevance
“…Cd is a highly toxic environmental contaminant. Organisms are equipped with Cd detoxification mechanisms, such as extrusion, chelation, and compartmentalization (Wysocki and Tamás, 2010;Wei et al, 2014;Luo et al, 2018). Yeast ATX1 was reported to chelate Cd 2+ as well as Cu + (Pufahl et al, 1997;Heo et al, 2012).…”
Section: Overexpression Of Osatx1 Increases CD Accumulation In the Shmentioning
confidence: 99%
“…Cd is a highly toxic environmental contaminant. Organisms are equipped with Cd detoxification mechanisms, such as extrusion, chelation, and compartmentalization (Wysocki and Tamás, 2010;Wei et al, 2014;Luo et al, 2018). Yeast ATX1 was reported to chelate Cd 2+ as well as Cu + (Pufahl et al, 1997;Heo et al, 2012).…”
Section: Overexpression Of Osatx1 Increases CD Accumulation In the Shmentioning
confidence: 99%
“…Sequencing and annotation studies identified thousands of plant defensins in rice (Kawahara et al, 2013). The quantitative trait locus of Cd accumulation in rice leaf 1 (CAL1) was mapbased cloned and was found to encode a defensin-like protein (Luo et al, 2018). CAL1 was functionally characterized as a positive regulator of Cd accumulation in rice leaves (Luo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several of the transporters involved in plant Cd accumulation have been identified, including, in Arabidopsis and rice: IRT1 (iron‐regulated transporter), Nramp1 (natural resistance‐associated macrophage protein) and OsNramp5 for Cd uptake, HMA3 (heavy metal ATPase) for Cd sequestration into vacuoles, AtNRAMP3/4 for Cd transport from vacuoles, HMA2, AtHMA4, OsLCT1 (low‐affinity cation transporter), and OsCAL1 (Cd accumulation in leaf) for Cd translocation and distribution (Mendoza‐Cozatl et al ; Clemens and Ma ; Luo et al ). Some signaling pathways, such as those for reactive oxygen species (ROS), nitric oxide (NO), gibberellin and auxin, have been reported to be involved in the transcriptional regulation of relevant transporter genes (Rodriguez‐Serrano et al ; Gallego et al ; Zhu et al ; Zhu et al ; Kawakami and Bhullar ), such as the gene encoding IRT1.…”
Section: Introductionmentioning
confidence: 99%